2011
DOI: 10.1097/nur.0b013e318233ea90
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio Use as a Tool to Demonstrate Professional Development in Advanced Nursing Practice

Abstract: A concrete way of recognizing and rewarding clinical leadership, excellence in practice, and personal and professional development of the advanced practice registered nurse (APRN) is lacking in the literature and healthcare institutions in the United States. This article presents the process of developing and evaluating a professional development program designed to address this gap. The program uses APRN Professional Performance Standards, Relationship-Based Care, and the Magnet Forces as a guide and theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…These results indicate that application of portfolios has a more positive impact on clinical competence than the conventional programs of continuing professional development and is consistent with other research performed in this area worldwide. For example, the results of the studies showed that reflection and completion of portfolio strengthen the critical approach in nurses' performance and foster ongoing professional development (Driessen et al ., 2005; Hespenheide et al ., 2011). Tochel et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicate that application of portfolios has a more positive impact on clinical competence than the conventional programs of continuing professional development and is consistent with other research performed in this area worldwide. For example, the results of the studies showed that reflection and completion of portfolio strengthen the critical approach in nurses' performance and foster ongoing professional development (Driessen et al ., 2005; Hespenheide et al ., 2011). Tochel et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the studies in this area have been conducted on nursing students with less focus on practicing nurses. In the United States, Hespenheide et al (2011) used the portfolio as a tool to demonstrate professional development of advanced practice registered nurses. Feedback from nurses involved in the study supports portfolio as a meaningful method to foster ongoing professional growth and development.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation